Influence of traffic noise from local and surrounding areas on high-rise buildings. (September 2020) - Benocci, R.; Bisceglie, A.; Angelini, F.; Zambon, G.
Abstract: Acoustic maps are, generally, calculated according to noise directives that evaluate the noise exposure levels of a population at a reference height of 4 m to provide values that correspond to the first floors of buildings. However, in large cities, the requirements for high-density housing, such as high-rise apartment buildings, make this evaluation incomplete. In this paper, we study noise propagation at different heights in the context of a medium-sized road network, such as that of Milan, Italy. Considering the "vertical housing" development trend for buildings in large cities, evaluation of the exposure of the population to noise at different heights becomes crucial, as residents might be subject to noise annoyances despite their distance from the source. Here, we present the results of noise measurements at three sites at different heights to observe the pattern of the noise profiles. A three-dimensional acoustic simulation reproducing the entire building structure of Milan was developed to estimate the noise levels generated by vehicle traffic sources at different heights. The predicted noise levels were compared with the measured data. In addition, over the entire urban area of Milan, we selected buildings higher than 50 m to analyse the variation of the noise level exposure at different heights. In this way, it could be possible to study this particular behaviour over a large scale. The results of this investigation may help plan and design new high-rise buildings to reduce the exposure of building dwellers to noise.